Humanizing higher education through innovative approaches for teaching and learning - Sengupta, Enakshi; Blessinger, Patrick; Makhanya, Mandla (Innovations in higher education teaching and learning, 2021)
As the demand for quality education grows, whilst resources are limited, innovative pedagogy is the only solution that can bridge both scarcity and quality. This edited collection showcases how innovative approaches to teaching and learning have become the need of the hour in higher education. How might new technologies and a fresh take on curriculum design create a sufficient impact on learners? Pouring renewed emphasis onto the practice of innovative pedagogy, the authors chronicle the success stories of fresh interventions, and demonstrate the potential impact of re-inventing the learner-centered approach. With insight from academics around the world, including action-based models, the authors address the challenges which they faced while implementing new and sometimes radical methods, and provide a roadmap for future change. Pooling a wealth of experience on how to create an efficient learning environment in today's competitive world, this book prepares educators, policymakers and other stakeholders to embrace transformational change within their institutions.